DEVELOPMENT OF TEACHING MATERIALS OF JEMBERS LOCAL WISDOM CROSSWORD PUZZLES FOR ELEMENTARY SCHOOL HIGHER CLASS STUDENTS - Faisma Isnaini Rizki Amalia; Suhartiningsih Suhartiningsih; Zetti Finali (Universitas Ahmad Dahlan, 2021)
This study aims to create a product in Indonesian language teaching materials by containing crossword puzzles of Jembers local wisdom that are valid, interesting, and effective when used by students during the learning process. The stages of the product development process adopt the 6-stage Design-Based Research (DBR) approach by Peffer et al. in Gems et al. (2016). The results of product validation and testing obtained the following data (a) the results of validation by validators and educators reached a percentage value of 86.6 with very feasible criteria, (b) the results of large-scale trials on products, the value of completeness of student learning outcomes reached a percentage of 92% with 93% of the total respondents giving a positive response to the teaching materials, and (c) the teaching materials developed were very valid, effective and interesting to use in the learning process based on the results of validation, student learning outcomes, and student responses toward the teaching materials